Comparative analysis of accuracy and time of calculation of wound surface area using mobile applications - Nikolai O. Mikhailov; Aleksandr A. Glukhov; Aleksandr A. Andreev; Anastasiya Yu. Laptieva; Oleg V. Sudakov; Vladimir Yu. Ivashkov; Aleksandr S. Denisenko (Наука и инновации в медицине, 2025)
Aim – to carry out a comparative assessment of the accuracy and time of calculating the area of the wound surface using mobile applications.